Desarrollo de un coagulante orgánico a partir de la semilla de moringa para ermpresa Comercial Dacetex Ltda (2020)
In the present grade work, the coagulant action of the Moringa Oleífera seed and the technical specifications of the equipment for the preparation of the coagulant at the industrial level is evidenced. The seed was evaluated with and without the extraction of its oil by a soxhlet equipment, due to its oil percentage it could reduce the formation of flocs. In addition to determine the moringa removal capacity, synthetic waste water was prepared with an initial turbidity of 277 NTU at different doses and pH values (acid, neutral and alkaline), where through an experiment design it was determined that the interaction between them influences the final turbidity and based on the results the coagulant was selected without oil extraction and a dose was obtained at an optimal dose of 40 mg/L at pH 7. Subsequently, tests were carried out on textile and domestic wastewater sources with an initial turbidity of 74.9 and 34.9 NTU respectively, in which the existence of a large amount of organic matter and chemical contaminants has been proven; compared with aluminum sulfate, removal percentages were obtained for textile water 65.89% and 62.18% for domestic wastewater. It is concluded that the Moringa Oleífera seed has a relatively high removal capacity with promising results that are represented in the low final turbidity values